2022
DOI: 10.1038/s41467-022-33425-3
|View full text |Cite
|
Sign up to set email alerts
|

Ni-catalyzed carbamoylation of unactivated alkenes for stereoselective construction of six-membered lactams

Abstract: Nitrogen-based heterocycles have aroused widespread interest due to their reoccurrence in many pharmaceuticals. Amongst these motifs, the enantioenriched lactams are the ubiquitous scaffolds found in myriad biologically active natural products and drugs. Recently, the transition metal-catalyzed asymmetric carbamoylation has been widely employed as a straightforward arsenal for chiral lactam architecture synthesis, including β-lactam and γ-lactam. However, despite the extensive efforts, there still remains no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 67 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Encouraged by these results, we explored several chiral ligands, L2-L8. The best performing ligand with regard to both substrate conversion and enantioselectivity was L1 (compare entry 5 with entries [6][7][8][9][10][11][12]. Next, we investigated the effect of the solvent and found that in CH 2 Cl 2 , Et 2 O, t BuOMe, toluene, and 2-methyltetrahydrofuran (2-Me-THF) the reaction proceeded with high enantioselectivity (entries 5 and 13-16), while in THF a racemic mixture of 2 a was formed (entry 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by these results, we explored several chiral ligands, L2-L8. The best performing ligand with regard to both substrate conversion and enantioselectivity was L1 (compare entry 5 with entries [6][7][8][9][10][11][12]. Next, we investigated the effect of the solvent and found that in CH 2 Cl 2 , Et 2 O, t BuOMe, toluene, and 2-methyltetrahydrofuran (2-Me-THF) the reaction proceeded with high enantioselectivity (entries 5 and 13-16), while in THF a racemic mixture of 2 a was formed (entry 17).…”
Section: Resultsmentioning
confidence: 99%
“…The interest in these compounds has prompted the development of various catalytic asymmetric methodologies for the synthesis of δ ‐lactam precursors. In the majority of these methods, which include N ‐heterocyclic carbene (NHC) catalysed cyclisations of α , β ‐unsaturated esters with sulfonylimines (Scheme 1a), [4] artificial metalloenzyme catalysed tandem C−H activation followed by a [4+2] annulation reaction (Scheme 1b) [5] and Ni‐catalysed carbamoylation of alkenes (Scheme 1c), [6] the cyclic structure of δ ‐lactam is assembled from two acyclic reaction partners. Another interesting strategy based on oxidative relay Heck arylation of enelactams was reported as well (Scheme 1d) [7] …”
Section: Introductionmentioning
confidence: 99%
“…A carbamoyl halide-tethered olefin may react with a carbon terminating reagent via cyclization and C-C coupling under redox-neutral or reductive conditions (Scheme 1C). [52][53][54][55][56][57][58][59][60][61] Alternatively, an aryl iodide-tethered olefin may react with an acylating reagent to fulfil the similar type of reaction. 62 More recently, the groups of Chu, 63 Stanley, 64 Wang, 65 Yuan 66 and other [67][68][69][70][71] have developed various methods for fully three-component racemic carboacylation of olefins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 2-piperidone is a fundamental scaffold for the synthesis of various chemical products, including high-value nylon-5 and nylon-6,5 (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 2-piperidone is a fundamental scaffold for the synthesis of various chemical products, including high-value nylon-5 and nylon-6,5 (2731). 2-piperidone is usually prepared from 5-aminovaleric acid (5AVA) as the substrate in biosynthetic pathways (32).…”
Section: Introductionmentioning
confidence: 99%